Bacterial vaccines in development 1 - Jansen, Kathrin (Henry Stewart Talks, 2015)
New bacterial vaccines in clinical development, Phases of vaccine development, Principles of vaccine antigen discovery & validation, Novel vaccines in development for Gram+ pathogens: C. difficile